Methodological principles of construction of an integrated automated system for management of educational institutions - Мужик, А.І. (Proceedings of National Aviation University (archive), 2008)
Substantive methodological provisions and technical requirements are formulated and grounded to the construction of integrated automated control system by establishments education as one of elements of the integrated informative environment of education and science of Ukraine.